Psychological and behavioural responses to death anxiety in older adults with chronic illnesses: a systematic integrative review - Alcântara, Leovaldo; Figueiredo, Teodora; Midão, Luís; Costa, Elísio; Paúl, Constança (Frontiers in Psychology, 2025)
BackgroundDeath anxiety has been identified as a relevant emotional response in older adults with chronic illness, but its role in shaping psychological and behavioural responses remains underexplored.ObjectiveThis integrative review aimed to investigate how death anxiety influences the emotional and behavioural responses of older adults living with chronic conditions, and to identify theoretical and clinical implications.MethodsA systematic search was conducted across PubMed, Scopus, Web of Science, and PsycINFO databases, using an integrative review framework. Nine studies met the inclusion criteria and were analysed using thematic synthesis and quality appraisal.ResultsDeath anxiety was associated with both negative and positive or adaptive outcomes, including emotional distress, avoidance behaviours, increased treatment adherence, and re-evaluation of personal values. Thematic analysis revealed five key domains: (1) psychological responses; (2) behavioural responses; (3) predictors and moderators; (4) spirituality as a buffer; and (5) assessment strategies.ConclusionDeath anxiety plays a central and context-dependent role in shaping health-related behaviours in later life. Its effects are moderated by factors such as spirituality, social support, disease burden, and emotional resilience. These findings support the development of integrative clinical models that combine existential and behavioural frameworks to improve adherence and well-being in older populations.